2021
DOI: 10.1111/ppa.13483
|View full text |Cite
|
Sign up to set email alerts
|

Application timing of herbicides, glyphosate and atrazine, sway respective epidemics of foliar pathogens in herbicide‐tolerant rapeseed

Abstract: Rapeseed (Brassica napus) production in Australia relies heavily on triazine‐or glyphosate‐tolerant cultivars. For 14 triazine‐tolerant cultivars, disease development of Neopseudocercosporella capsellae (white leaf spot), Alternaria brassicae and A. japonica (Alternaria leaf spot), and Hyaloperonospora brassicae (downy mildew) were all dependent upon herbicide application timing (p < 0.001), with significant differences between cultivars (p < 0.001) and a significant interaction (p < 0.001) between herbicide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The timing of herbicide application may factor into susceptibility to disease. Murtza et al [ 24 ] tested the impacts of the herbicides glyphosate and atrazine on canola susceptibility to the foliar fungal diseases Neopseudocercosporella capsellae , Alternaria brassicae, A. japonica , and Hyaloperonospora brassicae. They found that the timing of the herbicide application impacted the fungal pathogen disease severity and incidence.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of herbicide application may factor into susceptibility to disease. Murtza et al [ 24 ] tested the impacts of the herbicides glyphosate and atrazine on canola susceptibility to the foliar fungal diseases Neopseudocercosporella capsellae , Alternaria brassicae, A. japonica , and Hyaloperonospora brassicae. They found that the timing of the herbicide application impacted the fungal pathogen disease severity and incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, glyphosate reduced infection of GR soybean with Asian soybean rust ( Phakopspora pachyrhizi ), ,, GR alfalfa with alfalfa rust ( Uromyces striatus ), and GR cotton with Rhizoctonia solani . Results were more variable with GR rapeseed and three diseases, two fungal and one oomycete: white leaf spot ( Neopseudocercosporella capsellae ), Alternaria leaf spot ( Alternaria brassicae and Alternaria japonica ), and downy mildew ( Hyaloperonospora brassicae ) . Einhardt et al insinuated that nickel ion and glyphosate act synergistically in reducing Asian soybean rust in GR soybean, but a more than additive effect was not proven .…”
Section: Target Sites Of Commercial Herbicides Found In Fungi That Ar...mentioning
confidence: 99%
“…69 Results were more variable with GR rapeseed and three diseases, two fungal and one oomycete: white leaf spot (Neopseudocercosporella capsellae), Alternaria leaf spot (Alternaria brassicae and Alternaria japonica), and downy mildew (Hyaloperonospora brassicae). 70 Einhardt et al insinuated that nickel ion and glyphosate act synergistically in reducing Asian soybean rust in GR soybean, but a more than additive effect was not proven. 71 Glyphosate applied at the V3 or V6 growth stages of GR soybean suppressed charcoal rot (Macrophomina phaseolina) in a tilled site and had no effect in a no-till site.…”
Section: Found In Fungi That Are Not Commercial Fungicide Targetsmentioning
confidence: 99%